Isolation and characterization of lactic acid bacteria from clarias macrocephalus (African Catfish) for potential probiotic purposes - Tengku Abdul Hamid, Tengku Haziyamin; Khan Chowdhury, Ahmed Jalal; Azhar, Nur Shazana (2010)
Lactic acid bacteria (LAB) play an important role in aquaculture to develop microbial control strategies since disease outbreaks are recognized as important constraints to aquaculture production and since the development of antibiotic resistance has become a matter of growing concern. In this study 50 bacterial isolates from the intestinal tract of Clarias Macrocephalus (African Catfish) were tested for the identification of LAB. Phenotypic characteristic was confirmed by Gram staining and identified by other biochemical test such as catalase reaction, lactose utilization and antimicrobial test. Out of the 50 isolates, 30 were Gram-positive cocci. All 30 isolates have the ability to utilize lactose as part of their metabolism process and showed negative reactions towards catalase test. LABs also produce a variety of compounds with antimicrobial activity, and one of them is termed bacteriocin. Bacteriocins are proteinaceous antimicrobial compounds that exhibit bactericidal activity against species closely related to the producer strain. The main screening method that has been used to screen for the antimicrobial activities of bacteriocin is disc diffusion assay. The bacteriocin demonstrated a broad spectrum antagonistic activity against Salmonella Thyphimurium.